Cyclic AMP stimulates platelet-derived growth factor B chain mRNA expression in murine macrophage cell lines - Elizabeth J. Kovacs; Susan VanStedum (Mediators of Inflammation)
Prostaglandin E2 plays a role in cytokine production presumably by altering intracellular levels of cAMP. In this paper, we report on the differential expression of cytokine genes in murine macrophages in response to stimulation with activators of cAMP. Macrophages were cultured with or without cAMP activators in the presence or absence of LPS. Prior to treatment, macrophages do not express interleukin-1β, but do express low levels of tumour necrosis factor α and platelet-derived growth factor B chain mRNAs. After culture with cAMP-inducers, including PGE2, dibutyryl cAMP and forskolin, PDGF B chain mRNA is induced. Forskolin, for example, induced expression PDGF B chain mRNA to a level ranging from 25% to 200% of the level induced by LPS in 6 h. In contrast, cAMP-inducers enhance the expression of IL-1β and TNF-α mRNAs, but only in the presence of LPS. The combination of forskolin and LPS does not appear to act synergistically on PDGF B chain mRNA levels, suggesting that LPS-stimulated effects are not mediated through a cAMP-dependent pathway. Furthermore, macrophages differentially express cytokine genes in response to treatment with inducers of intracellular cAMP.